Thermosetting resin composition with phosphorus-containing flame retardant as well as preparation method and application of thermosetting resin composition
The thermosetting resin composition with a phosphorus-containing flame retardant addresses the challenge of achieving high flame retardancy and mechanical strength in PCBs, forming a stable carbonized layer to delay combustion and reduce toxic gas emissions, suitable for high-frequency and high-speed applications.
Patent Information
- Application Number
- CN202411451631.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-27
AI Technical Summary
Existing PCB materials face challenges in achieving high flame retardancy without toxic gas emissions, while maintaining mechanical properties and heat resistance, especially in high-frequency and high-speed applications.
A thermosetting resin composition incorporating a phosphorus-containing flame retardant, comprising modified maleimide and polyphenylene ether resins, along with silicon dioxide or talc fillers, forms a stable carbonized layer at high temperatures, enhancing flame retardancy and mechanical properties.
The composition improves flame retardancy, reduces harmful gas emissions, increases glass transition temperature, and enhances mechanical strength, making it suitable for high-frequency and high-speed printed circuit boards.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of resins, and in particular relates to a thermosetting resin composition with a phosphorus-containing flame retardant, a preparation method and application thereof. Background Art
[0002] Flame retardancy is crucial in printed circuit board (PCB) design. It can effectively slow down the spread of flames, protect electronic equipment from fire damage, and ensure that the circuit will not become a source of fire when a fault or overload occurs. In addition, good flame retardancy also helps to comply with strict safety standards and protect electronic equipment. As electronic equipment develops towards high performance and miniaturization, the materials and processes of PCBs are also facing new challenges, especially their flame retardancy.
[0003] In the traditional PCB manufacturing process, halogen-containing flame retardants are often used to improve the flame retardancy of materials. However, these substances release toxic and corrosive gases when burned, which poses potential hazards to the environment and human health. Therefore, stricter environmental regulations and increased environmental awareness have prompted the industry to find more environmentally friendly flame retardant solutions. Currently, a popular alternative is to use phosphorus-containing flame retardants. These flame retardants can form a protective layer at high temperatures, effectively slowing down the heat release rate of the material and reducing the risk of PCB combustion. At the same time, phosphorus-containing flame retardants can also increase the glass transition temperature of PCBs and enhance their stability in high temperature environments, thereby expanding the application range of PCBs in various electronic products. In addition, they also help reduce the water absorption rate of PCBs, reduce the damage caused by moisture to electronic components, and ensure the reliability and durability of electronic equipment in different environments.
[0004] CN1319124A discloses a resin composition, wherein mica and an organic phosphate compound are used to synergistically form a modified polyphenylene ether reinforced with flame-retardant glass fiber to obtain a modified polyphenylene ether having better flame retardancy. However, the modified polyphenylene ether has the following disadvantages: (1) the heat deformation temperature of the modified polyphenylene ether is reduced, resulting in the product being easily deformed at a higher temperature, affecting its normal use; (2) mica can reduce the impact strength of the modified polyphenylene ether and reduce the mechanical properties.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the objects of the present invention is to provide a thermosetting resin composition having a phosphorus-containing flame retardant.
[0007] A second object of the present invention is to provide a method for preparing a thermosetting resin composition having a phosphorus-containing flame retardant.
[0008] The third object of the present invention is to provide a glass cloth-based copper-clad laminate made using the above-mentioned thermosetting resin composition with a phosphorus-containing flame retardant, which has excellent flame retardancy, heat resistance and mechanical properties and is suitable for the production of high-frequency and high-speed printed circuit boards (PCBs).
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] A thermosetting resin composition with a phosphorus-containing flame retardant comprises two components, the phosphorus-containing flame retardant and a resin composition, wherein:
[0011] The structure of the phosphorus-containing combustion improver is shown in the following formula (I):
[0012]
[0013] Wherein m, n are positive integers ≥ 1, wherein R1 or R2 in the formula is any one of the following structural formulas 1 or 2 or a combination of both:
[0014]
[0015]
[0016] The phosphorus-containing flame retardant is 10 to 30 parts by weight;
[0017] The resin composition comprises the following components by weight:
[0018] 50-150 parts of modified maleimide resin;
[0019] 50-150 parts of modified polyphenylene ether resin;
[0020] 50-100 parts of filling material;
[0021] 15-25 parts of cross-linking agent;
[0022] Initiator 0.2-3 parts;
[0023] The modified maleimide resin is a bismaleimide resin having a structure of formula (II):
[0024]
[0025] Wherein, R1 is selected from any one of the following structural formulas 3 to 11 or a combination of two or more thereof:
[0026]
[0027] R2 is selected from any one of the following structural formulas 12 to 20 or a combination of two or more thereof:
[0028]
[0029] More preferably, the compound (B1) used in the present invention has a structural formula as shown in formula (III):
[0030]
[0031] The modified polyphenylene ether resin has a structure as shown in formula (IV):
[0032]
[0033] The structure of X is any one of the following structural formulas 21 to 24 or a combination of two or more thereof:
[0034]
[0035] In the formula (IV), R1 or R2 is at least one of a hydroxyl group, a vinyl group, an allyl group, an acrylic group, and a methacrylic group.
[0036] The modified polyphenylene ether resin is methacrylate modified polyphenylene ether.
[0037] The filler material is silicon dioxide, mica or talc, preferably spherical silicon dioxide.
[0038] The crosslinking agent is any one or more of a trialkenyl isocyanurate compound, a multifunctional acrylate compound, a multifunctional methacrylate compound, a multifunctional vinyl compound or a divinylbenzene compound.
[0039] The polymerization initiator is at least one of azobisisobutyronitrile, azobis(2-isopropyl)butyronitrile, azobishexamethylenedicarbonitrile, dibenzoyl peroxide, dimethylbenzoyl peroxide, diisopropyl peroxide, diisopropylbenzene peroxide, cyclohexanone peroxide, methyl ethyl ketone peroxide, dicyclohexyl peroxide, benzoic acid peroxide, tert-butyl peroxide, butylbenzoic acid peroxide or tert-butylbenzoic acid peroxide.
[0040] A method for preparing a thermosetting resin composition having a phosphorus-containing flame retardant, comprising:
[0041] Step 1: fully mixing the components of the resin composition and the phosphorus-containing flame retardant in a solvent until the resin is completely dissolved to obtain an adhesive;
[0042] Step 2: The adhesive obtained in step 1 is evenly coated on the glass fiber cloth by a glue coating machine, and dried and cured to volatilize the solvent to obtain a prepreg;
[0043] Step 3: Lay the prepreg obtained in step 2 on the copper foil and press them to obtain a glass cloth-based copper foil-clad board;
[0044] The solvent is at least one of toluene, butanone, acetone, dimethylformamide, methyl ethyl ketone or propylene glycol methyl ether.
[0045] The linear speed of the gluing machine is 8-25 m / min; the drying and curing temperature is 110-230° C.; the pressing pressure is 70-600 psi, the temperature is 70-240° C., the vacuum degree is 0.02-0.1 MPa, the curing time is 50-130 min, and the pressing time is 70-200 min.
[0046] The specifications and dimensions of glass cloth based copper clad laminates are 36×48, 37×49, 40×48, 40.5×48.5, 41×49, 42.5×48.5, and 43×49 (unit: inches).
[0047] The glass fiber cloth is of E grade, and the specifications are 1035, 1078, 1080, 2113, 2116, and 3313.
[0048] The copper foil is 1 / 3oz, Hoz, 1oz, 2oz, 3oz, 4oz or RTF copper foil.
[0049] A use of a thermosetting resin composition containing a phosphorus-containing flame retardant, wherein the glass cloth-based copper-clad plate produced therefrom is suitable for producing a high-frequency and high-speed printed circuit board (PCB).
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] 1. The present invention uses a modified phosphorus-containing flame retardant to improve the flame retardant properties of the material. Phosphorus elements promote the formation of a stable carbonized layer at high temperatures. This carbonized layer can effectively isolate oxygen and heat transfer, thereby delaying the combustion process of the material. At the same time, the addition of the modified phosphorus-containing flame retardant of the present invention not only enhances the stability of the material under extreme conditions, but also helps to reduce the release of harmful gases during combustion, meeting environmental protection requirements.
[0052] 2. The resin composition of the present invention adopts a modified maleimide and modified polyphenylene ether system, which effectively improves the material properties. This combination optimizes the heat resistance, chemical resistance and mechanical strength of the resin. By introducing the specific modified maleimide of the present invention, not only the glass transition temperature of the resin is increased, the thermal expansion coefficient is reduced, and the heat resistance is improved. DETAILED DESCRIPTION
[0053] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] The present invention provides a bismaleimide resin composition having the following structural formula:
[0055]
[0056] The components and trade names of the bismaleimide resin, polyphenylene ether resin, crosslinking agent, initiator, filler, flame retardant and filling material used in the present invention are shown in Table 1.
[0057] The present invention will be further explained and illustrated by specific embodiments below:
[0058] 1. The specific preparation method of the resin composition of the present invention is as follows:
[0059] A. Add butanone and toluene into the reactor according to the formula in Table 1, turn on the high-speed stirrer at a speed of 1500 rpm, keep stirring continuously and control the tank temperature at 45°C;
[0060] B. Add different resins into the reaction kettle according to the formula in Table 1. After adding, continue stirring for 60 minutes until the resin is completely dissolved to obtain a resin composition.
[0061] 2. The preparation method of the resin glue of the present invention is as follows:
[0062] A. Add flame retardant and filler into the reactor according to the formula in Table 1, turn on the high-speed stirrer at a speed of 1800 rpm, and continue stirring for 60 minutes after the addition is completed;
[0063] B. Add initiator into the reactor according to the formula in Table 1. After adding, start the cooling water circulation and keep the speed at 1500rpm. Control the tank temperature at 45℃ and continue stirring for 180 minutes. The resin glue is ready.
[0064] 3. The method for preparing the prepreg of the present invention is as follows:
[0065] A. The gluing baking temperature is 140℃-160℃, and the gluing speed is 10m / min;
[0066] B. Use 2116E-glass fiberglass cloth;
[0067] C. The prepreg resin content is adjusted according to the required glass cloth-based copper-clad laminate thickness;
[0068] 4. The preparation method of the glass cloth-based copper-clad laminate of the present invention is as follows:
[0069] A. Glass cloth based copper clad laminate stacking structure The number of prepregs is determined as required. Table 1 shows one of the stacking structures.
[0070] B. The metal foil used for the glass cloth-based copper-clad laminate is selected as needed. Table 1 describes RTF copper foil;
[0071] C. The lamination parameters of the glass cloth-based copper-clad laminate are adjusted as needed. The lamination conditions described in Table 1 are:
[0072] Vacuum pressure 50Torr; pressure 1.2-1.5MPa; hot plate temperature 150-220℃; curing time 200min.
[0073] The samples in Examples 1-6 and Comparative Examples 1-2 were tested for various properties according to the following methods:
[0074] (i) Glass transition temperature (Tg): The peak temperature of Tan δ was measured by a dynamic mechanical analysis (DMA) as the glass transition temperature.
[0075] (ii) Peel strength (PS): According to the standard of IPC-TM-650-2.4.8, the peel strength of the sample was tested using a universal tensile testing machine.
[0076] (III) 288°C heat resistance test (T288): A 8 mm × 8 mm copper foil substrate was placed on a thermal mechanical analyzer (TMA). The temperature was raised from room temperature to 288°C at a heating rate of 10°C / min and then maintained at 288°C. The dimensional changes of the sample were observed and the time of plate explosion after 288°C was recorded.
[0077] (iv) Thermal expansion coefficient: The thermal expansion coefficient of the sample shall be measured using a TMA instrument in accordance with the standards specified in IPC-TM-650 2.4.24;
[0078] (V) Dielectric constant (D k ) and dielectric loss factor (D f ): The dielectric constant and dielectric loss factor test methods are in accordance with the test specified in IPC-TM-650 2.5.5.9;
[0079] (VI) Flame retardancy: Sample test pieces with a size of 130 mm × 12.5 mm were taken and, according to the UL94 standard, 5 test pieces were subjected to 2 combustion tests respectively. The flame retardancy was evaluated by the sum of the duration of combustion during the combustion test;
[0080] (VII) Cracking temperature (Td): Select a square sample with a size of 6.35 mm × 6.35 mm and a minimum sample weight of 30 mg, bake it at 110 ± 2 °C for 24 hours, and cool it to room temperature in a desiccator. Use a thermogravimetric analyzer (TGA) to increase the temperature from room temperature to 450 °C at a rate of 10 °C / min. Record the percentage of weight loss of the sample as the temperature rises. The temperature at which the weight loss is 5% is reported as Td.
[0081] (VIII) PCT: The samples were subjected to a boiling test in a pressure cooker. The plates were boiled continuously for 120 min at 0.105 MPa and 120°C in a pressure cooker and then immersed in a 288°C tin furnace to observe the stratification and bubbling time. Samples with a stratification time of less than 5 min were evaluated as ×, and samples with a stratification time of more than 5 min and less than 10 min were evaluated as ○.
[0082] Table 1
[0083]
[0084]
[0085] Combining Table 1, we can see that
[0086] 1. Compared with the comparative example, the present invention adopts the modified phosphorus-containing flame retardant to improve the flame retardant properties of the material. The phosphorus element promotes the formation of a stable carbonized layer at high temperature. This carbonized layer can effectively isolate oxygen and heat transfer, thereby delaying the combustion process of the material and greatly improving the flame retardant properties of the material. At the same time, the addition of the modified phosphorus-containing flame retardant of the present invention not only enhances the stability of the material under extreme conditions, but also helps to reduce the release of harmful gases during combustion, which meets environmental protection requirements.
[0087] 2. Compared with the comparative example, the resin composition of the present invention adopts the modified maleimide and modified polyphenylene ether system, which effectively improves the material properties, specifically optimizes the heat resistance, chemical resistance and mechanical strength of the resin. By introducing the modified maleimide, not only the glass transition temperature of the resin is increased, the thermal expansion coefficient is reduced, and the heat resistance is improved.
Claims
1. A thermosetting resin composition having a phosphorus-containing flame retardant, characterized in that: The invention comprises two components: a phosphorus-containing flame retardant and a resin composition, wherein: The structure of the phosphorus-containing combustion improver is shown in the following formula (I): Wherein m, n are positive integers ≥ 1, wherein R1 or R2 in the formula is any one of the following structural formulas 1 or 2 or a combination of both: The phosphorus-containing flame retardant is 10 to 30 parts by weight; The resin composition comprises the following components by weight: 50-150 parts of modified maleimide resin; 50-150 parts of modified polyphenylene ether resin; 50-100 parts of filling material; 15-25 parts of cross-linking agent; Initiator 0.2-3 parts; The modified maleimide resin is a bismaleimide resin having a structure as shown in formula (II): Wherein, R1 is selected from any one of the following structural formulas 3 to 11 or a combination of two or more thereof: R2 is selected from any one of the following structural formulas 12 to 20 or a combination of two or more thereof: The modified polyphenylene ether resin has a structure as shown in formula (IV): The structure of X is any one of the following structural formulas 21 to 24 or a combination of two or more thereof: In the formula (IV), R1 or R2 is at least one of a hydroxyl group, a vinyl group, an allyl group, an acrylic group, and a methacrylic group.
2. A thermosetting resin composition with a phosphorus-containing flame retardant as claimed in claim 1, characterized in that: The modified maleimide resin is shown in the following formula (III):
3. A thermosetting resin composition with a phosphorus-containing flame retardant as claimed in claim 1, characterized in that: The filling material is silicon dioxide, mica or talc.
4. A thermosetting resin composition with a phosphorus-containing flame retardant as claimed in claim 1, characterized in that: The crosslinking agent is any one or more of a triolefin isocyanurate compound, a multifunctional acrylate compound, a multifunctional methacrylate compound, a multifunctional vinyl compound or a divinylbenzene compound; The polymerization initiator is at least one of azobisisobutyronitrile, azobis(2-isopropyl)butyronitrile, azobishexamethylenedicarbonitrile, dibenzoyl peroxide, dimethylbenzoyl peroxide, diisopropyl peroxide, diisopropylbenzene peroxide, cyclohexanone peroxide, methyl ethyl ketone peroxide, dicyclohexyl peroxide, benzoic acid peroxide, tert-butyl peroxide, butylbenzoic acid peroxide or tert-butylbenzoic acid peroxide.
5. A method for preparing a thermosetting resin composition having a phosphorus-containing flame retardant as claimed in claims 1 to 4, characterized in that: Step 1: fully mixing the components of the resin composition and the phosphorus-containing flame retardant in a solvent until the resin is completely dissolved to obtain an adhesive; Step 2: The adhesive obtained in step 1 is evenly coated on the glass fiber cloth by a glue coating machine, and dried and cured to volatilize the solvent to obtain a prepreg; Step 3: Lay the prepreg obtained in step 2 on the copper foil and press them to obtain a glass cloth-based copper foil-clad board; The solvent is at least one of toluene, butanone, acetone, dimethylformamide, methyl ethyl ketone or propylene glycol methyl ether.
6. The method for preparing a thermosetting resin composition having a phosphorus-containing flame retardant according to claim 5, characterized in that: The linear speed of the gluing machine is 8-25 m / min; the drying and curing temperature is 110-230° C.; the pressing pressure is 70-600 psi, the temperature is 70-240° C., the vacuum degree is 0.02-0.1 MPa, the curing time is 50-130 min, and the pressing time is 70-200 min.
7. The method for preparing a thermosetting resin composition having a phosphorus-containing flame retardant according to claim 5, characterized in that: The specifications and sizes of glass cloth-based copper-clad laminates are 36×48, 37×49, 40×48, 40.5×48.5, 41×49, 42.5×48.5, and 43×49; The glass fiber cloth is of E grade, with specifications of 1035, 1078, 1080, 2113, 2116, and 3313; The copper foil is 1 / 3oz, Hoz, 1oz, 2oz, 3oz, 4oz or RTF copper foil.
8. Use of a thermosetting resin composition having a phosphorus-containing flame retardant as claimed in claims 1 to 4, characterized in that: The glass cloth-based copper-clad board produced by the invention is suitable for producing high-frequency and high-speed printed circuit boards (PCBs).
Citation Information
Patent Citations
Flame resistant polyphenylene ether compositions
CN1319124A
